2020
DOI: 10.1029/2020jb019584
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Fluid Pressurization Effects on Frictional Stability of Shale Faults Reactivated by Hydraulic Fracturing in the Changning Block, Southwest China

Abstract: A shale fault reactivated during multistage hydraulic fracturing in the Changning block in the Sichuan Basin, southwest China, accompanied a cluster of small earthquakes with the largest reaching ML ~ 0.8. We illuminate the underlying mechanisms of fault reactivation through measurements of frictional properties on simulated fault gouge under hydrothermal conditions. Velocity‐stepping experiments were performed at a confining pressure of 60 MPa, temperatures from 30 to 300°C, pore fluid pressures from 10 to 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 67 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…The gouge SSC3740‐2 shows a higher tectosilicate content but a lower phyllosilicate content than the gouge SSC3730‐1. Compared with many previous research works (An, Zhang, Chen, et al, 2020; Chen et al, 2015; Fang et al, 2018; Kohli & Zoback, 2013), the mineral compositions are shown to be an important factor for shale fault stability.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The gouge SSC3740‐2 shows a higher tectosilicate content but a lower phyllosilicate content than the gouge SSC3730‐1. Compared with many previous research works (An, Zhang, Chen, et al, 2020; Chen et al, 2015; Fang et al, 2018; Kohli & Zoback, 2013), the mineral compositions are shown to be an important factor for shale fault stability.…”
Section: Discussionmentioning
confidence: 68%
“…As the depth of the target reservoir increases, the potential for fault instability and hazard of induced seismicity will increase dramatically. Although temperature is not the main factor controlling seismicity in the shallow shale reservoirs (An, Zhang, Chen, et al, 2020), the high temperature can impact the fault stability in deep shale reservoirs. Additionally, the mineral composition of the deep Longmaxi shale reservoir varies significantly and may also favor velocity‐weakening behavior at increased depths.…”
Section: Discussionmentioning
confidence: 99%
“…We observe that the microseismic events from these three stages are all far away from the perforation locations. The multistage events overlap and converge into a microseismic event band, which conforms to the characteristics of fault activation [34][35][36][37][38]. The microseismic event band coincides with fault #1 spatially, and its extension direction is also consistent with the strike of fault #1.…”
Section: Geomechanical Probability Analysismentioning
confidence: 65%
“…Deformation of the formation will occur because of CO 2 injection. Considering the existence of shale the bedding plane, natural fractures, and faults [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], the deformation behavior and the effect on fluid transport will be extremely complicated. The reactivation potential of faults does exist, Lithosphere which may provide a leak path for CO 2 to escape the storage formation [54][55][56].…”
Section: Discussionmentioning
confidence: 99%